Análise experimental de vigas de concreto armado com estribos plásticos - ALMEIDA, Francisco Carlos Franca de (2016)
The use of new technologies in civil construction market grows every year. In order to supply the needs of this department, several products are presented in fairs and congresses as alternatives to generate costs reduction in production and execution of building works. In parallel, small industries of civil construction market provide a polymer-based (plastic) stirrup, selling it through the internet, to use in the reinforced concrete beams and pillars as a replacement for those made of steel, with the promise of costs reduction and the guarantee of efficiency, according to data from national laboratories. But it needed to be confirmed, since the applications in these structures are still unknown by the majority of professionals of this area. Moreover, the brazilian standard on reinforced concrete, NBR 6118 (ABNT, 2014), released by the Brazilian Association for Technical Standards, brings no reference to the utilization of polymer-based stirrups. To check the mechanical properties and the safety of this product, polymer-based stirrups with rectangular shape (100 mm x 250 mm) were used in beams and tested at the Civil Engineering Laboratory located in the Federal University of Para. A total of 7 reinforced concrete beams were made, having a cross section of 140 mm x 290 mm and 2200 mm in length, 1 with steel bracket for reference, 3 with plastic stirrups and 3 with steel and plastic straps alternating every 150 mm, 100 mm and 75 mm. The beams with plastic stirrups had the same longitudinal reinforcement as the reference beam. The plastic stirrups were used to study its behavior as shear reinforcement. The STUTTGART test setup was used during the procedure. The experimental results obtained from the tests with plastic stirrups indicate inefficient and unsatisfactory performance compared to conventional steel stirrups since its contribution to withstand shear forces was practically negligible in relation to the reference beam.